A conserved MTMR lipid phosphatase increasingly suppresses autophagy in brain neurons during aging - Kovács, Tibor (2023)
Ageing is driven by the progressive, lifelong accumulation of cellular damage. Autophagy (cellular self-eating) functions as a major cell clearance mechanism to degrade such damages, and its capacity declines with age. Despite its physiological and medical significance, it remains largely unknown why autophagy becomes incapable of effectively eliminating harmful cellular materials in many cells at advanced ages. Here we show that age-associated defects in autophagic degradation occur at both the early and late stages of the process. Furthermore, in the fruit fly Drosophila melanogaster, the myotubularin-related (MTMR) lipid phosphatase egg-derived tyrosine phosphatase (EDTP) known as an autophagy repressor gradually accumulates in brain neurons during the adult lifespan. The age-related increase in EDTP activity is associated with a growing DNA N6-adenine methylation at EDTP locus. MTMR14, the human counterpart of EDTP, also tends to accumulate with age in brain neurons. Thus, EDTP, and presumably MTMR14, promotes brain ageing by increasingly suppressing autophagy throughout adulthood. We propose that EDTP and MTMR14 phosphatases operate as endogenous pro-ageing factors setting the rate at which neurons age largely independently of environmental factors, and that autophagy is influenced by DNA N6-methyladenine levels in insects.